PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP RESPON INVESTOR DALAM SEKTOR ANEKA INDUSTRI - Mutiara Vannetia (Business Accounting Review, 2015)
The purpose of this study was to know whether there was significant affects of corporate social responsibility disclosure which was measured by using the global reporting initiative 3.1 towards the investor response measured by using the abnormal return. The sample used in this study were 124 company years in the miscellaneous industry sector during the period of 2008-2012. The results of this study showed that Corporate Social Responsibility did not significantly affect the abnormal return. ROA and firm size as control variables had positive influence on abnormal return . While the control variables Debt to Equity Ratio and Market Share had no affect on abnormal returns